FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KECELAKAAN KERJA PADA PEKERJA KONSTRUKSI DI PROYEK RENOVASI RUMAH IBADAH MEDAN SIMALINGKAR TAHUN 2023 - Sihotang, Pita Rolasna Br Hotang (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Occupational accidents in the context of occupational safety and health are divided into three, namely incident, near miss, and accident. Occupational accidents and diseases that often occur in the construction sector are often due to inexperienced, seasonal and migrant workers. The type of research used is Quantitative Research using a Cross-Sectional approach. This research was carried out at the Medan Simalingkar House of Worship Renovation Project. The time of the research starts from November 2022 to March 2023. The population in this study are all construction workers who are registered as workers in the Medan Simalingkar House of Worship Renovation Project, all of which are the research sample, namely 60 workers. There is a relationship between Knowledge, Attitudes, Use of PPE, Work Period and Work Accidents in the Medan Simalingkar Worship Project and there is no relationship between Worker Age and Work Accidents in the Medan Simalingkar House of Worship Project. the variable use of PPE is the variable most related to work accidents in the Medan Simalingkar Worship Project. The use of service PPE has the potential to cause work accidents 8,636 times at the Medan Simalingkar House of Worship Project. For Vendors, it is suggested that Vendors conduct training and counseling about K3 to increase knowledge and increase worker awareness about the importance of K3, it is hoped that companies can pay attention to the provision of PPE for their workers and the need for supervision of the implementation of the rules for using PPE and the need for making K3 posters, as well as signs -signs warning of hazards in workplaces, especially those that have the potential to cause work accidents as well as awarding and sanctioning K3 violations in the workplace, especially related to the use of PPE.